2014
DOI: 10.1097/qai.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tuberculosis Treatment on Virologic and Immunologic Response to Combination Antiretroviral Therapy Among South African Children

Abstract: Background: Many HIV-infected children are diagnosed with tuberculosis (TB), but the effect of TB treatment on virologic and immunologic response to combination antiretroviral therapy (cART) is not well documented. Methods: Secondary analysis of a prospective cohort of cART-naïve HIV-infected South African children aged 0-8 years initiating cART to assess the effect of TB treatment at time of cART initiation on virologic suppression (HIV RNA <50 copies/mL), virologic rebound (HIV RNA >1000 copies/mL after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…Fourth, our results also show good immune recovery, with a 10% increase in CD4 percentage, from 20% at baseline to 30% in median at 6 months. This result is comparable to those of other cohorts of children receiving ART in Africa [ 23 , 33 , 34 ]. We did not find an association between VS and factors found in other studies such as age, gender, previous exposures to PMTCT or to maternal ART, baseline WHO stage, CD4 percentage, or baseline viral load [ 23 , 35 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…Fourth, our results also show good immune recovery, with a 10% increase in CD4 percentage, from 20% at baseline to 30% in median at 6 months. This result is comparable to those of other cohorts of children receiving ART in Africa [ 23 , 33 , 34 ]. We did not find an association between VS and factors found in other studies such as age, gender, previous exposures to PMTCT or to maternal ART, baseline WHO stage, CD4 percentage, or baseline viral load [ 23 , 35 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…Children who initiated ART while on TB treatment were almost 5 times more likely to develop major PI mutations than children without TB or who had completed TB treatment prior to ART initiation. Several studies have demonstrated worse virological outcomes in children who received TB co-treatment at the time of ART initiation, but this had not been linked to the presence of drug resistance [ 16 , 58 60 ]. TB co-treatment may predispose patients to drug resistance since the large pill burden may impair adherence and rifampicin-induced cytochrome P450 activity may cause sub-therapeutic levels of LPV [ 9 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies which used a higher viral load cut-off (400 copes/ml) found that TB-ART co-treatment decreased frequency of viral suppression [27], we failed to find an association in sensitivity analyses using this higher cut-off. Both studies; however, have noted that the impact of TB co-treatment varies by ART regimen, with the limited impact of TB co-treatment on viral load suppression among CHIV receiving NNRTI-based regimens, in contrast to CHIV on PI-based regimens, which may have inferior virologic and immunologic responses with TB co-treatment [26,27]. In our study, CHIV receiving PI-ART had a lower frequency of viral suppression than those receiving NNRTI-based regimens in univariate but not in multivariate analyses and was associated with decreased CD4 þ recovery in multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Growth trajectories between CHIV with and without TB-HIV co-treatment may differ because of the differential growth effects of TB disease and its resolution or because of side effects of TB medications. The few studies that have evaluated HIV-TB co-infected children had inconsistent findings [26,27] regarding the impact of co-treatment on viral suppression or immunologic responses in CHIV. A better understanding of viral suppression and the pattern of growth reconstitution during TB-HIV co-treatment can inform treatment approaches and nutritional monitoring and supplementation strategies.…”
Section: Introductionmentioning
confidence: 99%